World approaching extinction: bio-diversities, human security and the amazon rainforest wildfires (2020)
Fire outbreaks have long played an important role in the formation of vegetation types in the Amazonia where the high moisture contents and dense canopies have historically made the Amazon rainforest extremely resistant to fire spread. However, the fires of 2019, which caused massive deforestation, have left the Amazon rainforest massively depleted of its biodiversity. While scholars have examined the propensity for the fire to spread, there is scanty literature on the long-term human security consequences of the fire on the environment and on humans. The fires were largely triggered by anthropogenic causes but spread as a result of climate change. In addition, the political dynamics of Brazil has accommodated and promoted agricultural and mining practices, which exacerbated and sustained the fire. The direct and indirect effects of the fire include loss of vegetation, loss of biodiversity, reduction in carbon stocks of the forest with potential consequences for global carbon cycle, eco-imbalance and threat to human security. To find a viable long-term solution to deforestation and achieve sustainable development in the Amazon, the underlying causes of the fires must be addressed. Affirmative actions are needed to be taken at both national and international levels while sensitization drive on the human insecurity consequences of forest fires must be pushed